The Relationship Between Social Environment And Sexual Behavior Of Students In Bandung - Yani, Tri Ardayani (Journal of health research and technology, 2026)
Background:. Students themselves have long been described as a group that is both vulnerable and actively involved in premarital sexual behavior. The social environment that a teenager has entered can also have the effect of putting pressure on friends who have not had sex. Research Method: quantitative. The population is Immanuel Health Institute Regular Class students. The sample in this study was 262 respondents using proportional random sampling technique. Data analysis uses Spearman rank. Research Results: Almost all respondents (85.5%) have a fairly good social environment. almost all respondents (74.4%) have good behavior. The p value obtained is 0.000, which means the significance value is <0.05, so it can be concluded that there is a relationship between the social environment and sexual behavior in regular class Immanuel Health Institute students. Conclusion: There is a relationship between the social environment and sexual behavior in regular class Immanuel Health Institute students. Suggestion: Institutions must have options that do not harm students, especially if the student concerned is a victim. For example, collaborating with social services, health services, or counseling institutions to provide guidance to students with certain cases.